The Effectiveness of Flash Card Media in Improving Students' English Vocabulary at SMP Negeri 2 Galesong Utara - Nurarisda; Yulianti Natsir, Ratu; Burhanuddin, Wildhan (Journal of Language Testing and Assessment, 2023)
The researcher aims to determine the effectiveness of using flashcards in improving students' English vocabulary by conducting pre-experimental research and making 7th grade students at SMP Negeri 2 Galesong Utara as the research location and taking samples with a total population of 214 7th grade students while the sample used was 25 students. The process of data collection using pre-test and post-test used multiple choice by analyzing data using SPSS. The results of this study found that the use of flashcard media in the learning process to improve students' English vocabulary that considered effective based on the data obtained where the mean score in the pre-test 44,28 and the post-test 71,60. It can be seen that the mean score of the post-test is higher than the mean score of the pre-test. And it is proven again from the results of the analysis of the "paired sample test" using SPSS with a significance value of 0.000 <0.05. Based on the decision making is if the significance value is < 0.05, then H0 is rejected and H1 is accepted. Based on these results, it can be concluded that flashcard media is effective in improving students' English vocabulary.